(untitled) (Research, Society and Development, 2021)
Staff turnover is a challenge for organizations. If not observed, it can have consequences, such as the costs of dismissing and replacing employees and reduced productivity. This research aims to identify the causes of turnover in the civil construction sector. Therefore, exploratory qualitative research was carried out in a municipality in the North of the state of Rio Grande do Sul, based on fifteen interviews conducted from a semi-structured script, which were analyzed using the content analysis technique. The categories explored were individual causes, organizational causes and causes external to organization. The results indicate the main causes of turnover in the civil construction sector: city moving, higher salary offer, inadequate behavior, lack of productivity, lack of commitment and professional attitude, unfinished activities, lack of buildings to start, increase in job vacancy, repetitive and stressful activities, pressure in the work environment.